PREDICTION OF REMAINING USEFUL LIFE FOR COMPONENTS IN SSC OF RSG-GAS BASED ON RELIABILITY ANALYSIS - Entin Hartini; Endiah Puji Hastuti; Geni Rina Sunaryo; Aep Saepudin; Sri Sudadiyo; Amir Hamzah; Mike Susmikanti (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2022)
In the maintenance system, efforts are needed to improve the effectiveness of the maintenance system and organization. For effective maintenance planning it is necessary to have a good understanding of the reliability and component availability of the system. For this reason, it is necessary to determine the remaining component life using Remaining Useful Life (RUL), so that maintenance tasks can be planned effectively. The purpose of this study is to determine the remaining life of the safety A component from SSC RSG-GAS based on reliability analysis. The method used in this paper is a statistical approach to estimating RUL. The Weibull hazard model is determined for modeling the hazard function so that it can be integrated in the reliability analysis. The model is verified using data from the safety A component from the SSC RSG-GAS. The results obtained from the analysis are useful for estimating the remaining useful lives of these components which can then be used to plan for effective maintenance and help control unplanned outages. The results obtained can be used for maintenance development and preventive repair planning.